PERAN POSYANDU DALAM PELAYANAN KESEHATAN MASYARAKAT - Susanti, Erwina (JURNAL MEDIA KESEHATAN, 2018)
Elderly health care coverage in Public Health Jalan Gedang as much (81.92%) and the number of elderly as many as 686 people. Visit the elderly who come to posyandu ranges from 41-53 people per month in 2016. The health center has two IHC Gedang Way consists of IHC Elderly Elderly Serayu Mandiri and Posyandu Elderly Peace. IHC has five cadres and participants 44 people. Elderly Posyandu cadre of Peace has five people, participants lansianya 50 people. IHC Elderly Peace has many achievements than Posyandu Elderly Serayu Mandiri The study design used in this research is descriptive qualitative method. Informants in this study as many as 10 cadres and 1 officer in charge Posyandu program. The study design used in this research is descriptive qualitative method. Knowledge Posyandu Elderly Peace found that IHC Elderly for seniors 60 years and older age range and Posyandu Elderly Serayu Mandiri that Posyandu Elderly age range of 40 years and above. Attitude Posyandu Elderly Peace mostly elderly support and integrated support Serayu Mandiri attitude. Kader Posyandu Elderly Peace and Posyandu Elderly Serayu Mandiri mostly not expect incentives. Kader Posyandu Elderly Peace mostly mentioned five systems the table properly and Posyandu Elderly Serayu Mandiri no mention of five tables with the right system. Expected to conduct refresher training or volunteers to knowledge about Posyandu cadres better, could improve the role in the service of Posyandu.